While Everything Was Changing: Sheik Mehmed Rashid Efendi and His Purely Turkish Mawlid - Abdullah Uğur; Ensar Karagöz (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
Rashid Efendi (d. 1945) witnessed the last years of the Ottoman Empire and the first years of the Republic and was a reciter of the Quran, a sheikh, and a linguist. He participated as a member in the first Turkish Language Congress while acting as the sheikh of Sertarikzâde Sufi Lodge in Eyüp, Istanbul. Although Rashid Efendi as a very prolific writer is seen to have written works in line with tradition, he also has works that he wrote after the Alphabet Reforms that he stressed as being purely in Turkish. Among these works is the mawlid Rashid Efendi titled Türkçe Doğum [The Birth of Turkish] in order not to use the actual word mawlid. Rashid Efendi tried not to include any Arabic or Persian words in this verse text in accordance with the period’s understanding of language usage. Despite all these different new features, Rashid Efendi’s mawlid is part of Türkiye’s long-standing mawlid tradition. This article will briefly discuss the biography of Rashid Efendi, introduce his mawlid titled Türkçe Doğum, of which only copy is currently known, and emphasize the connection of the work to the mawlid tradition as well as the so-called purely Turkish words used in the work.